PENGARUH STRUKTUR AKTIVA DAN RETURN ON ASSETS TERHADAP DEBT RATIO (Studi Kasus Pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Periode 2008-2010) - Puspitawati, Lilis (Jurnal Riset Akuntansi, 2015)
Debt Ratio plays a role in companies because it gives information about the proportion of debt use to pay every assets of the company. In determining Debt Ratiocomposition, the company can consider factors influencing Debt Ratio, such as AssetsStructure and ROA. The aim of this research is to find out the influence of AssetsStructure and ROA toward Debt Ratio in mining companies listed in BEI 2008-2010period. The method used in this research is analysis method descriptive andverification. Technique to determine data is using secondary data obtained fromdocumentation. The samples in this research used purposive sampling method. Theannual financial statements used are from 15 mining companies of 2008-2010 forabout 45 samples. The employed statistics test is multiple linier regression andhypotheses test using F and T-test. These tests use SPSS 20.0 for Windowsapplication help.The results showed that Assets Structure affects positively to Debt Ratio, andROA affects negatively to Debt Ratio. The conclusion of this research Assets Structureaffects significantly to Debt Ratio, and ROA affects significantly to Debt Ratio. AssetsStructure and ROA have strong relation and affects significantly to Debt Ratio in miningcompanies.